The Other Labor Reform (Observatorio Económico, 2013)
We have witnessed one of the longest strikes on record at the Civil Registry (Registro Civil, Chile's civil registration and identification service): 18 working days or, in practice, the entire month of September. The workers obtained significant promotions, and the institution's budget for the next two years has been committed. Citizens have had to forgo their right to civil identity and to freedom of movement. The country's municipal employees are now on strike, with the likelihood of a public health crisis caused by accumulated garbage as the most salient unintended effect. Continue reading...
Keywords: Labor reform; Strikes